Corporate Responsibility in the Field of Sustainable Development on the Example of India - T. A. Goroshnikova (Мир новой экономики)
The relevance of national approaches to the study of corporate responsibility in the field of sustainable development is based not only on the expansion of methodological tools for assessment, but also on the need to provide it with a global perspective. Of particular interest is the study of corporate responsibility in developing countries that lag behind in terms of adoption but have distinct national characteristics. India, as the first country to oblige its companies to allocate funds for corporate social responsibility (CSR), demonstrates its intentions to form a national concept of sustainabledevelopment. The BRICS partnership between Russia and India provides opportunities for deeper co-operation in the field of sustainable development in general and corporate responsibility in particular. The paper chooses reports related to sustainable development and corporate social responsibility expenditures, as well as public initiatives of Indian companies as objects of research. An indicator characterising the national corporate approach to sustainable development is proposed.